Workforce Diversity: Gender, Education, and Ethnicity Affecting Organizational Perceived Performance in Nepalese Banking Sector- A Binary Logistic Regression Modeling - Thapa, Roshan (Nepal Journal of Multidisciplinary Research, 2023)
The organization performs well when its diverse workforce works properly. Inclusiveness of workforce diversity namely gender, education, and ethnicity are highly important for better organizational performance. The objective of this study is to measure the impact of workforce diversity on the organizational performance of the Nepalese Banking Sector of Newroad Branches. The strata of managerial level, officer level, and assistant level are developed and 128 samples are taken for the purpose of the study with the stratified random sampling method. Binary Logistic Regression is used as a major statistical tool to analyze the organization's performance against not performing. Through analysis, gender diversity, education diversity, and ethnicity have a positive impact and help to increase organization performance, who believe diversity helps to perform better in the organization. For an organization diversity among employees must be there for the well-being of the organization.